Personality and Counterproductive Work Behaviour (CWB) at AEON Tebrau, Johor Bahru - Tahir, Wan Nurul Aziera Ameera Wan Mohamad; Baharun, Mohamad Hafifi; Omar, Arenawati Sehat Hj (School of Social Sciences, USM, 2017)
Limited study regarding the factors contribute to counterproductive work behaviour (CWB) has been directed in investigating whether the Big Five Personality are the predictors of counterproductive work behaviour such as organizational constraints, co-worker performance failure and supervisor pressure. More specifically, the researcher examined whether there is relationship between Big Five Personality (i.e. conscientiousness, agreeableness, neuroticism, openness to experience and extraversion) with CWBs. Other than that, Counterproductive work behaviour (CWB) usually consists of explicit acts such as aggression and theft, or conversely, of more subtle and passive actions, such as willingly failing to fulfil tasks, carelessly following instruction, or doing work incorrectly. Generally, these kinds of matter have negative impacts either individually or towards an organization itself because it can be as a limitation of organization to achieve goal oriented purpose. Regarding this issue, personality of an individual can be as elements in this problem. Among of these five traits personality, there are some have the major contributions towards counterproductive work behaviour in the organization. Thus, this research is conducted to uncover the association between personalities and counterproductive work behaviour.